Liquid Crystals and Display Technology - Sasani Ghamsari, Morteza; Carlescu, Irina (IntechOpen, 2020)
Liquid crystals have attracted scientific attention for potential applications in advanced devices. Display technology is continuously growing and expanding and, as such, this book provides an overview of the most recent advances in liquid crystals and displays. Chapters cover such topics as nematic liquid crystals, active matrix organic light-emitting diodes, and tetradentate platinum(II) emitters, among others.